Water and salinity balances for irrigated agriculture in Pakistan - Kijne, Jacob W. (International Irrigation Management Institute, 1996)
Describes a streamlined approach to calculating water and salinity balances in three different irrigated areas of Pakistan where salinity is a major problem. Explores the impact of current irrigation and agronomic practices on salinity and suggests corrective measures.